Treatment of Psoriasis - Weinberg, Jeffrey M.; Weinberg, Jeffrey M. (Milestones in Drug Therapy,, 2008)
Psoriasis is an inherited skin disease that has been diagnosed in 4.5 million adults in the United States. About 10 percent to 30 percent of people with psoriasis also develop psoriatic arthritis, which causes pain, stiffness and swelling in and around the joints. The book reviews the clinical manifestations of these two entities. The main focus is on the evolving paradigm of therapy. Topical and ultraviolet therapy are discussed first, followed by traditional systemic therapy. A major focus is on biologic therapies. New agents in development are also reviewed. The book concludes with an evaluation of the quality of life impact of this disease. This volume provides an in-depth overview of the current state of psoriasis and its management. It is of interest to clinicians, researchers, and even patients who wish to learn more. It is also of interest to those in the pharmaceutical industry, and those in finance who cover the pharmaceutical field.